Biological and chemical forms in controlling oral biofilms - Bamofleh, Samar A.; Almuammar, Mohammed S.; Osseil, Aljawhara I. Bin; Alorf, Roaa A.; Alqhtani, Sultan M.; Alsadah, Amal A.; Abdullah, Sarah M.; Ganboa, Donya E.; Abualkhair, Basil F.; Khojah, Mohammed A.; Alhawsawi, Bashaer M. (International Journal Of Community Medicine And Public Health, 2022)
Although there have been many advances in the medical field regarding disease control and management, it has been demonstrated that certain diseases and infections still represent a significant challenge. For example, the presence of oral biofilms indicates the virulence of the underlying infection in different dental infections diseases, including peri-implantitis, periapical periodontitis, periodontitis, gingivitis, and dental caries. We have discussed various mechanical, chemical, and biological modalities that can be applied to control biofilms and limit plaque formation and secondary caries. Although physical brushing might be efficacious in cleaning, evidence indicates that it cannot eradicate the underlying bacteria. Accordingly, using biological and chemical materials is essential to achieve adequate disinfection and enhance the outcomes. Many modalities have been proposed in the literature, such as nanomaterials, organic compounds such as arginine, dietary substances, and the various chemical oral cleansers discussed in the current study. Bacteriophages are also promising in this context. However, they need further exploration regarding their efficacy and safety. In addition, resistance against these compounds is a serious issue and needs to be addressed in future research.